2000
DOI: 10.1161/01.hyp.36.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Skin Color and Blood Pressure in Egyptian Adults

Abstract: Abstract-In many, but not all societies, dark skin color is associated with high blood pressure. Whether the association between skin color and blood pressure is independent of known determinants of blood pressure remains controversial. We examined the association between skin color and blood pressure in 835 Egyptian adults (370 men and 465 women) participating in the National Hypertension Project, a national survey of hypertension prevalence and blood pressurerelated complications conducted in Egypt during 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
13
1
Order By: Relevance
“…These findings cast doubt on previous suggestions that skin color reflects genetic susceptibility to high blood pressure (Boyle, 1970;Gleiberman et al, 1999) or that skin color and blood pressure are linked physiologically (Harburg et al, 1978;Mosley et al, 2000). Both the genetic and the physiologic hypotheses predict a positive association between skin pigmentation and blood pressure.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…These findings cast doubt on previous suggestions that skin color reflects genetic susceptibility to high blood pressure (Boyle, 1970;Gleiberman et al, 1999) or that skin color and blood pressure are linked physiologically (Harburg et al, 1978;Mosley et al, 2000). Both the genetic and the physiologic hypotheses predict a positive association between skin pigmentation and blood pressure.…”
Section: Discussioncontrasting
confidence: 62%
“…None of these studies reported an association between pigmentation and blood pressure across the entire sample, after controlling for age, sex, and socioeconomic status. Klag et al (1991) found an association only in the lowest socioeconomic group, while Mosley et al (2000) reported an association only in Egyptian women. By contrast, the only studies that observed a consistent association between skin color and blood pressure across the sample measured skin color with some form of observer rating (Costas et al, 1981;Gleiberman et al, 1995;Harburg et al, 1973Harburg et al, , 1978Sichieri et al, 2001).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations